National Health Interview Survey, 1991 ([Verlag nicht ermittelbar], 1993)
The basic purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. Household variables in this data collection include type of living quarters, size of family, number of families in household, and geographic region. Person variables include sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. The Condition, Doctor Visit, and Hospital Record files contain information on each reported health condition, doctor visit within a two-week period, and hospitalization (12-month recall), respectively.